2005
DOI: 10.2320/matertrans.46.2659
|View full text |Cite
|
Sign up to set email alerts
|

Zincoaluminophosphate Molecular Sieves with AFI and ATS Topologies: Synthesis by Dry-Gel Conversion Methods and Their Catalytic Properties in the Isopropylation of Biphenyl

Abstract: Zincoaluminophosphates, ZnAPO-5 and ZnAPO-36 with AFI and ATS topologies, were successfully synthesized by dry-gel conversion (DGC) method: vapor-phase transport (VPT) and steam-assisted conversion (SAC) methods. ZnAPO-5 was synthesized successfully at 175 C by VPT and SAC methods using Et 3 N as structure directing agent (SDA). ZnAPO-36 was also obtained by VPT and SAC methods using Pr 3 N as SDA. The heating protocol was a key factor for the crystallization in the synthesis of ZnAPO-36: the best result was o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
8
0

Year Published

2007
2007
2020
2020

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 18 publications
(8 citation statements)
references
References 27 publications
0
8
0
Order By: Relevance
“…[35] However,s everale lements have been subjectt o rigorous study by employing advanced spectroscopict echniques, which have confirmed framework incorporation. [36] Metal-substituted AlPO-5 materials have been tested as catalysts in severalr eactions, including methanol to hydrocarbons, [37] ethylation and propylation of aromatics, [38,39] cracking of alkanes, [40] and aromatic isomerization. [41] In this work, we aim to study the effect of metal incorporation into the AlPO-5 structure and the effect of the created BAS on the MTH reaction.…”
Section: Introductionmentioning
confidence: 99%
“…[35] However,s everale lements have been subjectt o rigorous study by employing advanced spectroscopict echniques, which have confirmed framework incorporation. [36] Metal-substituted AlPO-5 materials have been tested as catalysts in severalr eactions, including methanol to hydrocarbons, [37] ethylation and propylation of aromatics, [38,39] cracking of alkanes, [40] and aromatic isomerization. [41] In this work, we aim to study the effect of metal incorporation into the AlPO-5 structure and the effect of the created BAS on the MTH reaction.…”
Section: Introductionmentioning
confidence: 99%
“…The metalloaluminophosphate analogs, MAPO-36 (M: Si, Mg, Zn) of ATS topology, also gave selectivities for 4,4 0 -DIPB of 20-40 % in the similar level as SSZ-55 [11,15,25]. Further, [Fe]-SSZ-24, with isomorphously substituted [Al]-SSZ-24 also gave the similar level of the selectivities for 4,4 0 -DIPB [26].…”
Section: The Effects Of Zeolite-type On the Isopropylation Of Bpmentioning
confidence: 90%
“…In contrast, no isomerization of 4,4 0 -DIPB occurred at the internal acid sites over H-MOR. [3][4][5] These selectivities for 4,4 0 -DIPB of SSZ-24 zeolites are in the similar level to those of SAPO-5 and MAPO-5 molecular sieves with the AFI topology, 11,[13][14][15] whereas the selectivity for 4,4 0 -DIPB is lower than those for H-MOR. [4][5][6][7][8] The differences in the selectivity for 4,4 0 -DIPB are due to the structural difference between H-MOR and molecular sieves with AFI topology.…”
mentioning
confidence: 81%
“…Our previous relevant findings on the subjects have been published on the alkylation of BP over H- [Al]-SSZ-31, 10 H-[Al]-CIT-5, 11 SAPO-5, 12 and MAPO-5 (M: Mg, Ca, Sr, Ba, and Zn). [13][14][15] H-[Al]-SSZ-24 zeolite is a high-silica large-pore molecular sieve, which is isostructural with AlPO 4 -5 (AFI topology), 16 and is expected to work as a potential catalyst for shape-selective alkylation of polynuclear aromatics because of its straight twelve-membered ring (12-MR) channel structure. SSZ-24 zeolite was first synthesized by Zones as its pure-silica form using 1-trimethylammonioadamantane as a structure-directing agent (SDA).…”
mentioning
confidence: 99%
See 1 more Smart Citation